2018
DOI: 10.1007/s11207-018-1278-5
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical Analysis of Solar Events Associated with Storm Sudden Commencements over One Year of Solar Maximum During Cycle 23: Propagation from the Sun to the Earth and Effects

Abstract: Taking the 32 storm sudden commencements (SSCs) listed by the International Service of Geomagnetic Indices (ISGI) of the Observatory de l'Ebre during 2002 (solar activity maximum in cycle 23) as a starting point, we performed a multi-criterion analysis based on observations (propagation time, velocity comparisons, sense of the magnetic field rotation, radio waves) to associate them with solar sources, identified their effects in the interplanetary medium, and looked at the response of the terrestrial ionized a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 90 publications
3
31
0
Order By: Relevance
“…IPs are related to ICMEs and we keep the two events in our study of the ICME shock deceleration. These events are important for space weather alerts as, at Earth and probably elsewhere, the sheath of the ICME can be more effective than the ICME itself (e.g., Kilpua et al, 2017;Bocchialini et al, 2018).…”
Section: Pairmentioning
confidence: 99%
See 2 more Smart Citations
“…IPs are related to ICMEs and we keep the two events in our study of the ICME shock deceleration. These events are important for space weather alerts as, at Earth and probably elsewhere, the sheath of the ICME can be more effective than the ICME itself (e.g., Kilpua et al, 2017;Bocchialini et al, 2018).…”
Section: Pairmentioning
confidence: 99%
“…In these three cases, v SunMess might be underestimated because of a wrong CME-ICME association, thus making ICME acceleration questionable. Bocchialini et al (2018) discusses the difficulties of correctly associating CMEs with ICMEs. There is no definitive evidence of ICME shock acceleration beyond Mercury's orbit in these six events.…”
Section: Icme Acceleration and Deceleration In The Interplanetary Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Kepler satellite showed that a great number of high energetic flares occurred in stars having large sunspot areas some with similar class as the sun (Maehara et al 2012). Besides a recent study by Bocchialini et al (2018) studying all the Storm Sudden commencement (SSC) registered in Dst variations during 2002 showed that the 37 largest SSCs were mainly related to 44 CMEs. 52% CMEs have a velocity larger than 900 km/s, 75% are halo CMEs.…”
mentioning
confidence: 97%
“…Watari (2018) identified and studied two geomagnetic storms associated with coronal holes within the 19 intense geomagnetic storms that occurred in Cycle 24. Bocchialini et al (2018) selected 32 SSC events during 2002 as a starting point and performed a multidata analysis based on observations to associate them with their solar sources, identify their effects in the interplanetary medium, and analyzed the response of the terrestrial ionized and neutral environment.…”
mentioning
confidence: 99%